Inhibition of RVLM synaptic activation at peak hyperthermia reduces visceral sympathetic nerve discharge - Hosking, Kimberley Gowens (Kansas State University, 2010)
Hyperthermia is an environmental stressor that produces marked increases in visceral sympathetic nerve discharge (SND) in young rats. The brainstem in rats contains the essential neural circuitry for mediating visceral sympathetic activation; however, specific brainstem sites involved remain virtually unknown. The rostral ventral lateral medulla (RVLM) is a key central nervous system region involved in the maintenance of basal SND and in mediating sympathetic nerve responses evoked from supraspinal sites. In the present study we tested the hypothesis that inhibition of RVLM synaptic activation at peak hyperthermia (internal body temperature, Tc, increased to 41.5°C) would affect heating-induced visceral sympathetic activation. Experiments were completed in chloralose-urethane anesthetized, baroreceptor-intact and sinoaortic-denervated, 3-6 month-old Sprague-Dawley rats. Bilateral inhibition of RVLM synaptic activation produced by muscimol microinjections (400 and 800 pmol) at 41.5°C resulted in immediate and significant reductions in peak heating-induced renal and splenic sympathoexcitation. Interruption of RVLM synaptic activation and axonal transmission by lidocaine microinjections (40 nmol) at 41.5°C produced significant reductions in hyperthermia-induced sympathetic activation to similar levels produced by RVLM muscimol microinjections. The total amount of SND inhibited by RVLM muscimol and lidocaine microinjections was significantly more during hyperthermia (41.5°C) than normothermia (38°C). These findings demonstrate that maintenance of sympathetic activation at peak hyperthermia is dependent on the integrity of RVLM neural circuits.
Keywords: Rostral Ventral Lateral Medulla; Sympathetic Nerve Discharge; Muscimol; Lidocaine; Acute Heat Stress; Biology, Neuroscience (0317)